Detection of Oxidative Stress-Induced Carbonylation in Live Mammalian Cells - Mukherjee, Kamalika (Free Radic Biol Med, 2015)
Oxidative stress is often associated with etiology and/or progression of disease conditions, such as cancer, neurodegenerative diseases, and diabetes. At the cellular level, oxidative stress induces carbonylation of biomolecules such as lipids, proteins and DNA. The presence of carbonylcontaining biomolecules as a hallmark of these diseases provides a suitable target for diagnostic detection. Here, a simple, robust method for detecting cellular aldehydes and ketones in live cells using a fluorophore is presented. A hydrazine-functionalized synthetic fluorophore serves as an efficient nucleophile that rapidly reacts with reactive carbonyls in the cellular milieu. The product thus formed exhibits a wavelength shift in the emission maximum accompanied by an increase in emission intensity. The photochemical characteristics of the fluorophore enable the identification of the fluorophore-conjugated cellular biomolecules in the presence of unreacted dye, eliminating the need for removal of excess fluorophore. Moreover, this fluorophore is found to be non-toxic and is thus appropriate for live cell analysis. Utility of the probe is demonstrated in two cell lines, PC3 and A549. Carbonylation resulting from serum starvation and hydrogen peroxide induced stress is detected in both cell lines using fluorescence microscopy and a fluorescence plate reader. The fluorescent signal originates from carbonylated proteins and lipids but not from oxidized DNA, and the majority of the fluorescence signal (>60%) is attributed to fluorophore-conjugated lipid oxidation products. This method should be useful for detecting cellular carbonylation in a high content assay or high throughput assay format.